The Adoption of Blended Learning in Non-Formal Education Using Extended Technology Acceptance Model - Kurniawan, Ridho; Pramana, Edwin; Budianto, Herman (Indonesian Journal of Information Systems, 2021)
This study aims to determine the influencing factors for understanding the intention of the learners in Non-Formal Education to use Blended Learning. In addition, it aims to investigate the relationships of the factors in a theoretical model. This study was conducted due to the lack of research in the world that discusses the adoption of Blended Learning in Non-Formal Education in Developing Countries such as Indonesia. Blended Learning at Non-Formal Education in the Covid-19 era is needed because the education institution has a limited place to accommodate more learners. A questionnaire based on google form was used to collect data. A sample of 566 users of Blended Learning from Non-Formal Education Institutions in Indonesia were used.  All variables from the theoretical model are measured using existing scales.  Structural Equation Model (SEM) was used to analyze the theoretical model.  SPSS and Amos were used as the software tools. This research contributes to the theoretical understanding of Blended Learning adoption as well as practice and provide guidance for Non-Formal Education to successfully implementing Blended Learning in their institutions. From the thirteen initial hypotheses, there are nine significant hypotheses. Three hypotheses with the largest magnitude are SI -> PU, CE -> PEU, and PU -> BI.  SI is the most influencing factor in the adoption of blended learning at non-formal education institutions.